2011
DOI: 10.1016/j.prevetmed.2011.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal investigation of protozoan parasites in meat lamb farms in southern Western Australia

Abstract: 14In this study, 96 faecal samples were collected from pregnant Merino ewes, at two broad-15 acre, commercial sheep farms in southern Western Australia, on two separate occasions 16 (16 and 2 weeks prior to lambing). Following lambing, 111 (Farm A) and 124 (Farm B) 17 female crossbred lambs (2 -6 weeks old), were individually identified using ear tags (a 18 numbered tag and a radio-frequency tag). A total of 1,155 faecal samples were collected 19 only from these individually identified lambs on five separate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
2
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 44 publications
5
39
2
2
Order By: Relevance
“…Ryan et al 2005;Yang et al 2009, Wang et al 2010bSweeny et al 2011b). In Australia, reported prevalences for ewes in Western Australia ranged from 6·3-8·3% (Sweeny et al 2011b) and for lambs from 9·3-56·3% on different properties (Ryan et al 2005;Yang et al 2009;Sweeny et al 2011a, b). A total of 9 species/genotypes of Cryptosporidium have been reported in sheep and lambs in Australia; C. parvum, C. hominis, C. xiaoi, C. bovis, C. ubiquitum, sheep genotype I, C. andersoni, pig genotype II, C. fayeri and C. suis and sheep genotype I (Ryan et al 2005;Giles et al 2009;Yang et al 2009;Robertson, 2009;Sweeny et al 2011a, b), with C. xiaoi and C. ubiquitum most common although Yang et al (2009) found high proportions of C. parvum isolates in pre-weaned sheep in Western Australia when a C. parvum-specific PCR was used.…”
Section: Sheepmentioning
confidence: 99%
“…Ryan et al 2005;Yang et al 2009, Wang et al 2010bSweeny et al 2011b). In Australia, reported prevalences for ewes in Western Australia ranged from 6·3-8·3% (Sweeny et al 2011b) and for lambs from 9·3-56·3% on different properties (Ryan et al 2005;Yang et al 2009;Sweeny et al 2011a, b). A total of 9 species/genotypes of Cryptosporidium have been reported in sheep and lambs in Australia; C. parvum, C. hominis, C. xiaoi, C. bovis, C. ubiquitum, sheep genotype I, C. andersoni, pig genotype II, C. fayeri and C. suis and sheep genotype I (Ryan et al 2005;Giles et al 2009;Yang et al 2009;Robertson, 2009;Sweeny et al 2011a, b), with C. xiaoi and C. ubiquitum most common although Yang et al (2009) found high proportions of C. parvum isolates in pre-weaned sheep in Western Australia when a C. parvum-specific PCR was used.…”
Section: Sheepmentioning
confidence: 99%
“…Cryptosporidium (including C. parvum) and Giardia were identified in all eight flocks included in the present study, and have been widely reported in sheep in Australia (Ryan et al, 2005;Yang et al, 2009;Sweeny et al, 2011;Sweeny et al, 2012a;Yang et al, 2014a;Yang et al, 2014b) and worldwide (Xiao 2010). Therefore the observations of reduced HSCW and dressing % associated with these organisms have important implications for sheep meat industries worldwide.…”
Section: Parvum (But Not All Cryptosporidium Spp)mentioning
confidence: 56%
“…DNA from samples from Western Australia was previously analysed using different primers as described in Sweeny et al (2011).…”
Section: Pcr Amplification -Cryptosporidium and Giardiamentioning
confidence: 99%
See 1 more Smart Citation
“…Distribuída no mundo todo, está última espécie foi isolada em seres humanos (ONG et al, 2002;XIAO, 2010), mas tem sido observada em cordeiros com menos de doze meses de idade (SANTÍN; FAYER, 2007;YANG et al, 2009;FURUSETH HANSEN, 2010;WANG et al, 2010;SWEENY et al, 2011). Subtipagem de sete isolados de C. parvum, baseados na análise da sequência do gene GP60, revelou a presença de cinco diferentes subtipos (IIaA17G1R1, IIaA16G1R1, IIdA20G1, IIdA24G1 and IIdA22G2R1) pertencentes a duas famílias de subtipos zoonóticos (IIa and IId).…”
Section: Criptosporidiose Em Ovinosunclassified